2023
DOI: 10.3389/fsurg.2023.1235120
|View full text |Cite
|
Sign up to set email alerts
|

Intercostal nerve cryoablation therapy for the repair of pectus excavatum: a systematic review

R. Scott Eldredge,
Lisa McMahon

Abstract: IntroductionThe minimally invasive repair of pectus excavatum (PE) is a painful procedure that can result in long-term hospitalization and opioid use. To mitigate the length of stay and opioid consumption, many different analgesia strategies have been implemented. The aim of this study is to review the use and patient outcomes of intercostal nerve cryoablation (INC) during PE repair reported in the literature.MethodsAn unfunded literature search using PubMed identifying articles discussing INC during PE repair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…This nding was supported by the literature review by Eldredge et al, which found that the overall complication rate was either signi cantly lower or no difference between the INC and non-INC cohorts. 4 While our study reported a slightly higher complication rate compared to other studies, we have implemented several practices to reduce this rate, including a comprehensive infection prevention protocol. Notably, all brachial plexus injuries in the INC group have fully recovered.…”
Section: Resultsmentioning
confidence: 70%
See 2 more Smart Citations
“…This nding was supported by the literature review by Eldredge et al, which found that the overall complication rate was either signi cantly lower or no difference between the INC and non-INC cohorts. 4 While our study reported a slightly higher complication rate compared to other studies, we have implemented several practices to reduce this rate, including a comprehensive infection prevention protocol. Notably, all brachial plexus injuries in the INC group have fully recovered.…”
Section: Resultsmentioning
confidence: 70%
“…1,2 PE results in an inward depression of the sternum and may lead to a decrease in cardiopulmonary tness and result in psychosocial distress. [3][4][5] Surgical correction of PE is commonly carried out via the Nuss procedure or the minimally invasive repair of pectus excavatum (MIRPE). [6][7][8] During MIRPE, a concave metal bar is placed behind the sternum and rotated into place resulting in an immediate remodeling of the chest wall resulting in signi cant postoperative pain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation